Genocias ir rezistencija Nr. 46(2) - Bubnys, Arūnas; Grickevičius, Artūras; Miknevičius, Gintautas; Zagreckas, Rimantas; Jurkutė, Mingailė; Kareniauskaitė, Monika; Klumbys, Valdemaras (Genocidas ir rezistencija, 2019)
Pilnas leidinys